Politics as a vocation in the African context? An African theological engagement with Max Weber - Kure, Kefas U. (HTS teologiese studies, 2022)
The German sociologist, Max Weber, argued that politics has to be taken as a vocation just like other fields of academic and professional engagements. He did this by reconsidering his earlier view on ethics of conviction, which he thought does not hold sufficient promise to address the political atmosphere of his day. To consolidate this proposal, Weber proposed an ethic of responsibility which, for him, carries some great promise to advance politics as a vocation. In this article, however, I engage with these thoughts and proposals by Weber in order to deduce some lessons on how politics could be considered as vocation. This was thought to carry some promise in the African context of political engagement in reducing misappropriation, mismanagement, and wastefulness of both human and material resources. This article concludes that taking politics as a vocation would enhance the placement of value on human lives over things as it is the case in the African context.Contribution: This contribution would ensure that individuals intending to take politics as a vocation have a different view of politics other than amassing wealth, but to render service to humanity.